ANTIBIOGRAM PATTERNS OF STAPHYLOCOCCAL SPECIES ISOLATED FROM HEALTHY INDIVIDUALS IN NILAI, NEGERI SEMBILAN, MALAYSIA - Himashi, Imanda Gurudeniya; Subramaniam, Geetha (Global Science Publications, 2018)
Antibiotic resistance is an alarming phenomenon worldwide, challenging the effectiveness of antibiotics which are used to treat infectious diseases. In this study, pure cultures of forty skin and nasal samples from healthy individuals in Nilai, Negeri Sembilan, were screened. Samples were inoculated on the nutrient agar plates to obtain single colonies, followed by sub-culturing and series of confirmatory tests such as Gram staining, catalase test, Mannitol Salt Agar, as well as cefoxitin disk-diffusion test to obtain pure MRSA and MRSE isolates. A total of 13 MRSA strains and one MRSE strain were obtained and subjected to antibiotic susceptibility testing on Mueller Hinton agar using Kirby-Bauer disk diffusion technique. All cefoxitin-resistant isolateswere resistant to penicillin G, erythromycin, linezolid, and vancomycin; 78% of them were resistant to teicoplanin, clindamycin, quinupristin/dalfopristin; 56% showed resistance to nalidixic acid and cefazolin while 33% of them showed resistance to cefuroxime. All isolates (100%) were susceptible to doxycycline, chloramphenicol, and ciprofloxacin. Eight different antibiogram patterns were obtained from these 14 isolates with resistance towards 11 out of 16 types of antibiotics used in this study. This finding which is a surveillance control method of antibiotic-resistant crisis is important as the results could provide an indication of the resistance patterns circulating among healthy individuals, and could contribute towards a more definitive antibiotic therapy of staphylococcal species infections in Malaysia